Exploring the role of COX-2 in Alzheimer's disease: Potential therapeutic implications of COX-2 inhibitors - Nathalie Moussa; Ninar Dayoub (Saudi Pharmaceutical Journal, 2023)
This review highlights the potential role of cyclooxygenase-2 enzyme (COX-2) in the pathogenesis of Alzheimer's disease (AD) and the potential therapeutic use of non-steroidal anti-inflammatory drugs (NSAIDs) in the management of AD. In addition to COX-2 enzymes role in inflammation, the formation of amyloid plaques and neurofibrillary tangles in the brain, the review emphasizes that COXs-2 have a crucial role in normal synaptic activity and plasticity, and have a relationship with acetylcholine, tau protein, and beta-amyloid (Aβ) which are the main causes of Alzheimer's disease. Furthermore, the review points out that COX-2 enzymes have a relationship with kinase enzymes, including Cyclin Dependent Kinase 5 (CDK5) and Glycogen Synthase Kinase 3β (GSK3β), which are known to play a role in tau phosphorylation and are strongly associated with Alzheimer's disease. Therefore, the use of drugs like NSAIDs may be a hopeful approach for managing AD.However, results from studies examining the effectiveness of NSAIDs in treating AD have been mixed and further research is needed to fully understand the mechanisms by which COX-2 and NSAIDs may be involved in the development and progression of AD and to identify new therapeutic strategies.